Endogenous real wage rigidity in a search frictions model. (9th June 2018) - Martin, Christopher; Wang, Bingsong
Abstract: The existing literature often incorporates ad hoc models of exogenous real wage rigidity into search frictions models of the labour market in order to match the large volatility of unemployment observed in the data. In this paper, we develop an alternative version of the search frictions model that incorporates insights from behavioural economics. We derive a model in which endogenous real wage rigidity emerges from optimal wage-setting and show that this model can match the observed volatility of unemployment. Thus our proposed model can match the data as closely as the existing literature but without the disadvantage of assuming exogenous and ad hoc forms of real wage rigidity.